Effects of Exercise Training on Fetuin-A in Obese, Type 2 Diabetes and Cardiovascular Disease in Adults and Elderly: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A (BioMed Central Ltd., 2019)
Background: Elevated levels of fetuin-A are associated with increased risks of metabolic syndrome, type 2 diabetes and nonalcoholic fatty liver disease. This meta-analysis investigated whether exercise interventions can reduce fetuin-A in adults. Methods: We searched clinical trials that objectively assessed fetuin-A and included study arms with exercise intervention. The pre-intervention and post-intervention data were used for meta-analysis. The effect sizes were calculated as standardized mean differences or changes in fetuin-A and expressed as Hedges g using random-effects models. Results: The overall Hedges g for fetuin-A in all included interventions was - 0.640 (95%CI - 1.129 to - 0.151; n = 9), but this effect was not observed in obese (g = - 0.096; 95%CI, - 0.328 to 0.135) and type 2 diabetes/dysglycemia (g = - 0.56; 95%CI, - 1.348 to 0.236) individuals. Additionally, the random-effects meta-regression analysis showed that there was not a greater decrease in fetuin-A in individuals who achieved greater body mass index reductions (regression coefficient = 0.065; 95%CI, - 0.185 to 0.315). Conclusion: Supervised exercise is associated with reductions in fetuin-A levels in adults and elderly. However, the results of the present meta-analysis should be interpreted with caution because of the variety of type of exercises and individual obesity related-disorders involve. Therefore, additional high-quality randomized controlled trials describing the effect of supervised exercise interventions on fetuin-A in adults are still needed. © 2019 The Author(s).